A dokumentumfilm-tervek piaci követelményeiről és ezek átalakulásáról – első rész - Róbert Lakatos (Symbolon)
The Variable Requirements of the Changing Documentary Film Market The international market of the documentary projects – the so called “pitching forums” – was formed about 30 years ago at the International Documentary Forum Amsterdam (IDFA) film festival. There the commissioning editors of different documentary TV slots could pre-buy the films at the level of project. Many documentaries could be made thanks to those pre-buys. After a while, many similar financing forums were formed in different countries, connected to different festivals, and they continue to play an important role regarding the documentary productions, although, due to the decreasing number of the documentary TV slots, it is more and more difficult to get financing at such forums. But they started to play an important role in the distribution of the films. Those who are not promoting their film at the level of project, have difficulties in the distribution of the completed film. This study is based on the personal experience of the author, who as film director and producer participated at preparation classes for different pitching forums, so he could observe not only the development of his projects, but also of the projects of the other participants. This study is also about the formal requirements of the documentary film projects presented at such pitching forums.